Cerebrolysin and repetitive transcranial magnetic stimulation (rTMS) in patients with traumatic brain injury: a three-arm randomized trial - Verisezan Rosu, Olivia; Jemna, Nicoleta; Hapca, Elian; Benedek, Irina; Vadan, Iulia; Muresanu, Ioana; Chira, Diana; Radu, Constantin; Cherecheş, Răzvan; Strilciuc, Stefan; Muresanu, Dafin (Frontiers in Neuroscience, 2023)
Traumatic brain injury (TBI) is a major public health problem affecting millions worldwide. Despite significant advances in medical care, there are limited effective interventions for improving cognitive and functional outcomes in TBI patients. This randomized controlled trial investigated the safety and efficacy of combining repetitive transcranial magnetic stimulation (rTMS) and Cerebrolysin in improving cognitive and functional outcomes in TBI patients. Ninety-three patients with TBI were randomized to receive either Cerebrolysin and rTMS (CRB+rTMS), Cerebrolysin and sham stimulation (CRB+SHM), or placebo and sham stimulation (PLC+SHM). The primary outcome measures were the composite cognitive outcome scores at three and six months after TBI. Safety and tolerability were also assessed. The study results demonstrated that the combined intervention of rTMS and Cerebrolysin was safe and well-tolerated by patients with TBI. Although no statistically significant differences were observed in the primary outcome measures, the descriptive trends in the study support existing literature on the efficacy and safety of rTMS and Cerebrolysin. The findings of this study suggest that rTMS and Cerebrolysin may be effective interventions for improving cognitive and functional outcomes in TBI patients. However, limitations of the study, such as the small sample size and exclusion of specific patient populations, should be considered when interpreting the results. This study provides preliminary evidence for the safety and potential efficacy of combining rTMS and Cerebrolysin in improving cognitive and functional outcomes in TBI patients. The study highlights the importance of multidisciplinary approaches in TBI rehabilitation and the potential for combining neuropsychological measurements and interventions to optimize patient outcomes. Further research is needed to establish these findings' generalizability and identify the optimal dosages and treatment protocols for rTMS and Cerebrolysin.